Domestic demand-side response on district heating networks. Issue 4 (19th May 2019) - Sweetnam, Trevor; Spataru, Catalina; Barrett, Mark; Carter, Edwin
ABSTRACT: Results are presented from a field study that deployed demand-shifting technology on a sample of 28 homes connected to a district heating (DH) network in England over the winter of 2015/16. The study's aim was to improve the load factor of the participating households. This has the potential to improve the attractiveness of DH and accelerate the roll out of DH networks. Capital costs are lowered by reducing required boiler capacity and pipework sizes. Operational costs are reduced by increasing the coverage of the primary plant and reducing heat losses and pumping energy. The interventions were found to increase the load factor of the participating homes from 0.29 to 0.44. This led to an increased energy demand of approximately 3%; however, the estimated network cost savings exceed this amount. While some participants noted the altered operation of their heating systems and expressed concern, the majority indicated they would be willing to participate in a commercial scheme for a small financial reward. In addition to specific insights for the deployment of demand shifting on DH networks, the results provide general lessons for the utilization of building thermal inertia for demand shifting.